Quo Vadis Myanmar?: Military Rule, the 2010 Election and Beyond (Journal of International Studies, 2020)
Myanmar (or formerly Burma) has been ruled by the military (tatmadaw) since 1962 and although multiparty elections were held in 1990, the Myanmar military junta simply refused to accept the results and transfer power to the National League Democracy (NLD) that won with a landslide victory. Instead, the Myanmar military junta announced its own version of political reform through the introduction of a â€œdisciplined democracyâ€ and as such convened a National Convention for the purpose of drafting a new constitution for the country. The constitution was finally approved in 2008 through a referendum that was highly rigged. Based on provisions of the 2008 Constitution, the military junta held another round of multiparty elections on 7 November 2010. Taking stock of events since 1988 and in the light of recent developments, this paper therefore attempts to gauge the future direction of the countryâ€™s political landscape by interpreting and analyzing recent events. More importantly, it would attempt to show how much change can be expected in Myanmar especially when taking into account a flawed Constitution, a highly rigged elections and a new pseudo-civilian government. In other words, is there going to be real political change or are the elections a mere window dressing by the countryâ€™s military junta?